2013
DOI: 10.3390/pharmaceutics5020318
|View full text |Cite
|
Sign up to set email alerts
|

Design and Exploratory Neuropharmacological Evaluation of Novel Thyrotropin-Releasing Hormone Analogs and Their Brain-Targeting Bioprecursor Prodrugs

Abstract: Efforts to take advantage of the beneficial activities of thyrotropin-releasing hormone (TRH) in the brain are hampered by its poor metabolic stability and lack of adequate central nervous system bioavailability. We report here novel and metabolically stable analogs that we derived from TRH by replacing its amino-terminal pyroglutamyl (pGlu) residue with pyridinium-containing moieties. Exploratory studies have shown that the resultant compounds were successfully delivered into the mouse brain after systemic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…While the prodrug did not perform significantly better than the direct administration of TRH in this paradigm under the experimental conditions employed [16,34] we feel that these exploratory results are encouraging especially in the context of potential preclinical therapeutic advantage considering the excellent in vitro stability of the prodrug in plasma (Table 2). Therefore, we anticipate that prodrug administration will be devoid of significant TRH exposure to the periphery in follow up studies.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…While the prodrug did not perform significantly better than the direct administration of TRH in this paradigm under the experimental conditions employed [16,34] we feel that these exploratory results are encouraging especially in the context of potential preclinical therapeutic advantage considering the excellent in vitro stability of the prodrug in plasma (Table 2). Therefore, we anticipate that prodrug administration will be devoid of significant TRH exposure to the periphery in follow up studies.…”
Section: Resultsmentioning
confidence: 83%
“…In the PST, the immobility represents a “depressive mood” and, when mice receive a test agent with antidepressant-like effect, the immobility time is reduced compared to that of the control group, as mice spend more time swimming in order to escape. TRH has been shown by us [6,13,16,34] and others [40] to exhibit such a central effect. As shown in Figure 2, a statistically significant decrease in the immobility time was established compared to mice receiving vehicle only (immobility time of 205 ± 4 s), when the prodrug was injected to the animals (immobility time of 176 ± 3 s).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several endogenous and synthetic TRH-like peptides with the pGlu-Xaa-Pro-NH 2 ([Xaa 2 ]TRH) sequence have been investigated, where Xaa denotes any natural and unnatural amino acid residues [20][21][22]. For example, [Glu 2 ]TRH (1b; Figure 1) exhibits various CNS actions characteristic to TRH without endocrine effects, which is preferable in the context of CNS drug development [23]. We have previously shown that, unlike TRH, this peptide did not increase acetylcholine (ACh) turnover in the rat hippocampus [24].…”
Section: Introductionmentioning
confidence: 99%